2006
DOI: 10.1042/cs20050353
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of tumour necrosis factor-α (TNF-α) in patients with Type II diabetes mellitus after myocardial infarction are related to endothelial dysfunction

Abstract: The pathophysiology of insulin resistance and atherosclerosis may share a common inflammatory basis, maintaining endothelial dysfunction, suggesting why patients with T2DM (Type II diabetes mellitus) have an impaired prognosis after an MI (myocardial infarction), but it remains unclear how these parameters are inter-related. Forty patients with an MI (20 patients with and 20 patients without T2DM) took part in this cross-sectional study. Endothelium-dependent [FMD (flow-mediated dilation)] and -independent [NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 44 publications
2
29
0
1
Order By: Relevance
“…Other studies showed how adiponectin can inhibit TNF-α mediated expression of E-selectin, VCAM-1 and ICAM-1 in human endothelial cells [47][48][49]51,52] . These findings furtherly confirm the vasoprotective action of adiponectin45 [53][54][55][56][57][58][59][60] and how this molecule may negatively modulate atherogenesis also by means its influence on inflammatory variables such as TNF-α.…”
Section: Inflammation Markers In Patients With Dfssupporting
confidence: 71%
See 1 more Smart Citation
“…Other studies showed how adiponectin can inhibit TNF-α mediated expression of E-selectin, VCAM-1 and ICAM-1 in human endothelial cells [47][48][49]51,52] . These findings furtherly confirm the vasoprotective action of adiponectin45 [53][54][55][56][57][58][59][60] and how this molecule may negatively modulate atherogenesis also by means its influence on inflammatory variables such as TNF-α.…”
Section: Inflammation Markers In Patients With Dfssupporting
confidence: 71%
“…Thus most of research experiences seem to suggest that atherosclerosis in diabetes could be a real inflammatory disorder. A study [60] evaluated the prevalence of inflammatory markers such as high-sensitivity CRP, adiponectin, and nuclear factor-κB (NF-κB) expression, in peripheral blood mononuclear cells in patients with type 2 diabetes mellitus (T2DM) with and without macrovascular disease. Authors reported how diabetic subjects with T2DM showed a higher hsCRP and NF-κB expression and a lower degree of adiponectin serum levels compared to healthy controls.…”
Section: Inflammation Markers In Patients With Dfsmentioning
confidence: 99%
“…in skeletal muscle (36,37), the heart (38 Á41) and adipose tissue (37,42,43). It also acts on endothelial cells (44,45) and on C-fibers (non-myelinated or very thinly myelinated sensory nerve fibres), which are made more sensitive by the action of TNF-a (46 Á 48). These effects (and similar effects caused by other cytokines) may help to explain skeletal symptoms and pain in patients suffering from influenza.…”
Section: Evolution Of Virulence Properties In Influenza Virusesmentioning
confidence: 99%
“…114 Winederived phenolic compounds have anti-inflammatory actions including inhibition of reaction oxygen species in neutrophils, monocytes and macrophages. 115,116 In subjects with diabetes, red wine consumption, taken with meals, significantly reduces oxidative stress and the circulating concentration of pro-inflammatory cytokines from lymphocytes and macrophages such as C-reactive protein, tissue necrosis factor-alpha and interleukin-6, as well as improving cardiac function after a myocardial infarction.…”
Section: Effect Of Wine On Diabetes Mellitusmentioning
confidence: 99%